Autophagy Contributes to the Rapamycin-Induced Improvement of Otitis Media - Xie, Daoli; Zhao, Tong; Zhang, Xiaolin; Kui, Lihong; Wang, Qin; Wu, Yuancheng; Zheng, Tihua; Ma, Peng; Zhang, Yan; Molteni, Helen; Geng, Ruishuang; Yang, Ying; et al. (Frontiers in Cellular Neuroscience, 2022)
Otitis media (OM) is a pervasive disease that involves hearing loss and severe complications. In our previous study, we successfully established a mouse model of human OM using Tlr2tm1Kir (TLR2–/–) mice with middle ear (ME) inoculation of streptococcal peptidoglycan-polysaccharide (PGPS). In this study, we found that hearing loss and OM infections in OM mice were significantly alleviated after treatment with rapamycin (RPM), a widely used mechanistic target of RPM complex 1 (mTORC1) inhibitor and autophagy inducer. First of all, we tested the activity of mTORC1 by evaluating p-S6, Raptor, and mTOR protein expression. The data suggested that the protein expression level of p-S6, Raptor and mTOR are decreased in TLR2–/– mice after the injection of PGPS. Furthermore, our data showed that both the autophagosome protein LC3-II, Beclin-1, ATG7, and autophagy substrate protein p62 accumulated at higher levels in mice with OM than in OM-negative mice. The expression of lysosomal-associated proteins LAMP1, Cathepsin B, and Cathepsin D increased in the OM mice compared with OM-negative mice. Rab7 and Syntaxin 17, which is necessary for the fusion of autophagosomes with lysosomes, are reduced in the OM mice. In addition, data also described that the protein expression level of p-S6, mTOR and Raptor are lower than PGPS group after RPM treatment. The accumulation of LC3-II, Beclin-1, and ATG7 are decreased, and the expression of Rab7 and Syntaxin 17 are increased significantly after RPM treatment. Our results suggest that autophagy impairment is involved in PGPS-induced OM and that RPM improves OM at least partly by relieving autophagy impairment. Modulating autophagic activity by RPM may be a possible effective treatment strategy for OM.